2021
DOI: 10.3389/fcell.2021.631272
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Stem/Progenitor Cell Subpopulations and Their Implications in Tendon Biology

Abstract: Tendon harbors a cell population that possesses stem cell characteristics such as clonogenicity, multipotency and self-renewal capacity, commonly referred to as tendon stem/progenitor cells (TSPCs). Various techniques have been employed to study how TSPCs are implicated in tendon development, homeostasis and healing. Recent advances in single-cell analysis have enabled much progress in identifying and characterizing distinct subpopulations of TSPCs, which provides a more comprehensive view of TSPCs function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 119 publications
(141 reference statements)
0
23
0
Order By: Relevance
“…It has been confirmed that Scx, Msi1, αSMA, Cd133, and Nes is present in perivascular TSPCs by immunostaining of the perivascular TSPCs isolated from human tendon microvessels ( Tempfer et al, 2009 ). A former study discovered some assertive evidence that TSPCs can also be explanted from adjoining tissues ( Huang et al, 2021 ). Besides, a study based on the zebrafish models revealed that totally ablating tendons could be well-restored by progenitors derived from neighboring tissues.…”
Section: Tendon Development Guidance For Tendon Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been confirmed that Scx, Msi1, αSMA, Cd133, and Nes is present in perivascular TSPCs by immunostaining of the perivascular TSPCs isolated from human tendon microvessels ( Tempfer et al, 2009 ). A former study discovered some assertive evidence that TSPCs can also be explanted from adjoining tissues ( Huang et al, 2021 ). Besides, a study based on the zebrafish models revealed that totally ablating tendons could be well-restored by progenitors derived from neighboring tissues.…”
Section: Tendon Development Guidance For Tendon Repairmentioning
confidence: 99%
“…Inflammation reaction is an important section of the tendon healing and may ultimately affect repair outcomes. The effects of HIF-2α, Prostaglandin E2 and IL-1β on TSPCs, promote enhanced expression of tenogenic genes ( Huang et al, 2021 ). After inflammatory stimulation, both embryonic and postnatal tendon cells exhibit similar tenogenic commitment, but the latter also expressed up-regulated catabolic enzymes and inflammatory mediators ( Li et al, 2019 ).…”
Section: Tendon Development Guidance For Tendon Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPCs differ from MSCs for their transcriptional profiles with higher tendon-related gene expression levels ( Tan et al, 2012 ). Many advances in the identification and characterization of distinct TSPC subpopulations have been made using single-cell analyses, giving a more complete view of the TSPC identity ( Harvey et al, 2019 ; Mienaltowski et al, 2019 ; Kendal et al, 2020 ; Huang et al, 2021 ). TSPCs have attracted a lot of attention playing a key role in tendon development, homeostasis, and healing ( Bi et al, 2007 ; Millar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, many other genes related to bone formation remain uncharacterized during IB development. The formation of IBs may undergo several processes including differentiation of tendon stem/progenitor cells (TSPCs) into osteoblasts, ossification, and mineralization [ 3 , 18 , 19 ]. Therefore, the genes involved in these processes are worth of exploration to better understand the formation of IBs.…”
Section: Introductionmentioning
confidence: 99%